Determinant of Income Inequality in Central Java Province - Alfariza Ramadhan; Herman Sambodo; Goro Binardjo; Arif Andri Wibowo (EKO-REGIONAL, 2023)
The purpose of this study is to analyze the effect of GRDP per capita, Investment, Human Development Index, Open Unemployment Rate on inter-regional income inequality in Central Java Province. This study uses secondary data in the form of panel data consisting of cross-time period 2010-2021 and cross-site 35 regencies/cities in Central Java Province. The approach method used to estimate this regression model is the FEM (Fixed Effect Model) approach method. The results of this study indicate that the variables of GRDP per capita and the Open Unemployment Rate (TPT) have a positive and significant effect on inter-regional income inequality, and the Human Development Index (HDI) variable has a negative and significant effect on inter-regional income inequality. Meanwhile, the Investment variable has no effect on inter-regional income inequality in Central Java province in 2010-2021